278 Phase I clinical trial evaluating the safety of ADP-A2M10 SPEAR T-cells in patients with MAGE-A10+ advanced non-small cell lung cancer. (10th December 2020) - Blumenschein, George; Devarakonda, Siddhartha; Johnson, Melissa; Moreno, Victor; Gainor, Justin; Edelman, Martin; Heymach, John; Govindan, Ramaswamy; Bachier, Carlos; Spéville, Bernard Doger de; Frigault, Matthew; Olszanski, Anthony; et al.
Abstract : Background: ADP-A2M10 SPEAR T-cells are genetically engineered autologous T-cells that express a high affinity MAGE-A10-specific T-cell receptor targeting MAGE-A10 + tumors in the context of HLA-A*02. This trial is now complete (NCT02592577 ). Methods: This first-in-human dose escalation trial utilized a modified 3+3 design to evaluate safety and antitumor activity. Eligible patients (pts) were HLA-A*02 + with advanced non-small cell lung cancer (NSCLC) expressing MAGE-A10. Pts underwent apheresis; T-cells were isolated, transduced with a lentiviral vector containing the TCR targeting MAGE-A10, and expanded. Pts underwent lymphodepletion (LD) with varying doses/schedules of fludarabine (Flu) and cyclophosphamide (Cy) prior to receiving ADP-A2M10. ADP-A2M10 was administered at Dose Level (DL) 1= 0.1×10 9, DL2 0.5–1.2×10 9, and DL3/Expansion= 1.2–15×10 9 transduced cells. Results: As of Jan 10, 2020, 11 pts (6 male/5 female) with NSCLC (3 squamous cell, 7 adenocarcinoma, 1 adenosquamous) were treated. Five, 3 and 3 pts received cells at DL1, DL2, and DL3/Expansion, respectively. The most frequently reported adverse events ≥ Grade 3 were lymphopenia (11), leukopenia (9), neutropenia (8), anemia (6), thrombocytopenia (5), and hyponatremia (5). Three pts reported CRS (Grades 1, 2, and 4, respectively). One pt received the highest dose of LD (Flu 30 mg/m 2 Day 1 4 and Cy 1800 mg/m 2 Day 1–2) prior to a second infusion and had a partial response (PR). This pt subsequently developed aplastic anemia and died. Responses included: 1 pt – PR, 3 pts - stable disease, 2 pts – progressive disease, 1 pt - too early to determine, 4 pts - off-study prior to tumor assessment. SPEAR T-cells were detectable in peripheral blood from pts at each dose level, and in tumor tissue from pts at DL1 and DL3. Conclusions: ADP-A2M10 SPEAR T-cells have shown acceptable safety and no evidence of toxicity related to off-target binding or alloreactivity. Given the minimal antitumor activity and the discovery that MAGE-A10 expression frequently overlaps with MAGE-A4 expression, the clinical program has closed. Several trials with SPEAR T-cells targeting MAGE-A4 are ongoing (https://bit.ly/35htsZK). Trial Registration: NCT02592577 Ethics Approval: The trial was conducted in accordance with the principles of the Declaration of Helsinki and the International Conference on Harmonization Good Clinical Practice guidelines and was approved by local authorities. An independent ethics committee or institutional review board approved the clinical protocol at each participating center. All the patients provided written informed consent before study entry.